Genome-wide identification, phylogeny, and expression analysis of the CA gene family in tomato. Issue 1 (1st January 2020) - Feng, Chao-Yang; Chen, Zhi-Feng; Pei, Ling-Ling; Ma, Su-Xian; Nie, Hong-Mei; Zheng, Shao-Wen; Sun, Sheng; Xing, Guo-Ming
Abstract: Genes in the carbonic anhydrase (CA) family encode zinc metalloenzymes that catalyze the reversible interconversion of carbon dioxide and water to bicarbonate and protons. Although CAs play key roles in diverse biological processes involving carboxylation and decarboxylation, including photosynthesis and respiration, plant growth and response to stress, the characteristics of CA gene family members in tomato remain unclear. In this study, we performed an exhaustive search of the tomato genome and accordingly identified 14 CA genes that are unevenly distributed on the 12 tomato chromosomes. We examined in detail the structures, conserved motifs, phylogenetic relationships and duplications of these genes, and for functional characterization, also undertook RNA-seq analyses to assess the transcript levels of CA genes in various tissues and organs and at different developmental stages. Furthermore, we investigated the expression patterns of the CA genes in response to salt stress. We found that some family members exhibited tissue-specific expression, whereas others were more ubiquitously expressed. Our results will provide a valuable foundation for further studies on the CA genes in tomato and other plants in the Solanaceae family.